Anthropogenic impacts upon plant species richness and NPP in California - Williams, J. W.; Seabloom, E. W.; Slayback, D.; Stoms, D. M.; Viers, J. H. (Ecology Letters, 2005)
We assess the importance of anthropogenic land-use, altered productivity, and species invasions for observed productivity-richness relationships in California. To this end, we model net primary productivity (NPP) c. 1750 AD and at present (1982-1999) and map native and exotic vascular plant richness for 230 subecoregions. NPP has increased up to 105% in semi-arid areas and decreased up to 48% in coastal urbanized areas. Exotic invasions have increased local species diversity up to 15%. Human activities have reinforced historical gradients in species richness but reduced the spatial heterogeneity of NPP. Structural equation modelling suggests that, prior to European settlement, NPP and richness were primarily controlled by precipitation and other abiotic variables, with NPP mediating richness. Abiotic variables remain the strongest predictors of present NPP and richness, but intermodel comparisons indicate a significant anthropogenic impact upon statewide distributions of NPP and richness. Exotic and native species each positively correlate to NPP after controlling for other variables, which may help explain recent reports of positively associated native and exotic richness.
Keywords: California; human impacts; Land cover change; net primary productivity; species richness; structural equation models